Influence of gas flow rate and sodium carboxymethylcellulose on foam properties of fatty alcohol sodium polyoxyethylene ether sulfate solution. Issue 7 (3rd July 2017) - Xu, Chaohang; Wang, Deming; Wang, Hetang; Zhang, Yi; Dou, Guolan; Wang, Qingguo
ABSTRACT: Foamability, foam initial liquid volume, and bubble size of fatty alcohol sodium polyoxyethylene ether sulfate (AES) surfactant solution were studied with and without the addition of sodium carboxymethylcellulose (CMC) at different gas flow rates, using a sparging method. The generation time decreased with increasing gas flow rate. At low gas flow rates, the added CMC greatly enhanced the foamability by preventing bubble collapse. The initial liquid volume of the foam first increased rapidly, and then gradually decreased. Increasing the CMC concentration increased the initial liquid volume of the foam. The mean bubble diameter first clearly decreased, then increased slowly with increasing gas flow rate. CMC showed different effects on bubble size at high and low gas flow rates. Adsorption of CMC on AES molecules forms a network structure and improves bubble film stability, which can explain the above results. These findings provide guidelines for generating foam with excellent properties suitable for coal mine dust control by adjusting the gas flow rate and the concentration of the added water-soluble polymer. GRAPHICAL ABSTRACT: